Physico-Chemical Studies on the Coordination Compounds of Thiazolidin-4-One - Dinesh Kumar; Amit Kumar; Jyoti Sharma (Journal of Chemistry)
A dry benzene solution of the Schiff base, N-(2-hydroxyphenyl)-3′-carboxy-2′-hydroxybenzylideneimine upon reacting with mercaptoacetic acid undergoes cyclization and forms N-(2-hydroxyphenyl)-C-(3′-carboxy-2′-hydroxyphenyl)thiazolidin-4-one, LH3 (I). A MeOH solution of I reacts with , , , and Mo ions and forms the monomeric coordination compounds, [Mn(LH)(MeOH)3] (II), [Cu(LH)(MeOH)] (III), [Zn(LH)(MeOH)] (IV), [FeCl(LH)(MeOH)2] (V), and [MoO2(LH)(MeOH)](VI). The coordination compounds have been characterized on the basis of elemental analyses, molar conductance, molecular weight, spectral (IR, reflectance, ESR) studies, and magnetic susceptibility measurements. I behaves as a dibasic tridentate OOS donor ligand in these compounds. The compounds are nonelectrolytes ( = 6.2–13.8 mho cm2 mol−1) in DMF. A square-planar structure for III; a tetrahedral structure for IV and an octahedral structure for II, V, and VI are suggested.